Simulation instead of Experience by using GeoGebra for the Physics Teacher: https://doi.org/10.69692/SUJMRD090163 - BOUNTHONG, Bounseng; VANGCHANGYIA, Somsack; THIPPHAPHONE, Kinnaly; VONGVILAY , Chanpheng; KEOMANYCHAN, Phonepadith (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The motivation to study physical sciences at all levels in Laos is a problematic challenge for which there are several reasons. One of the core reasons is the teaching method, with too much theory. To understand physical sciences well you have to complement theory with practical experiments. But most schools or high schools lack the proper technical resources such as a laboratory, not enough equipment, the lack of qualified personnel to assist in a laboratory setup and preparation and the upgrading and replacement of teaching resources. These problems can be solved by the use of computer software to do the laboratory and practical experimentation. The software we are talking about is GeoGebra, which is free educational software that is suitable for colleges, high schools and universities. The software package can simulate many things for example: forces and movement, optics, waves, … without the use of expensive equipment which requires regular maintenance and calibration, … we can place the simulation online and send it to students to practice at their own pace at home. Fortunately, most of the high schools in the center of the province have computers, in addition some students have smartphones, and they are used to using their smartphones so we will use this strong point to attract and motivate students little by little to learn physical sciences. This can be achieved by sending activities and homework to their smartphones. Training is required as the use of certain software is not obvious. For the best results for both teachers and students, it is essential to train well before application to the classroom environment. We provided simulation training with GeoGebra to 17 physics teachers from the northern provinces, which we found to be a great fit for them, but they found it very useful to learn and adapt to the current situation. To use in teaching and learning, we introduced how to use the simulation in teaching and learning in two schools in Luangprabang. It revealed that the opinion of 35 teachers on the use of the simulation in the teaching is very good. Students' satisfaction with the use of simulation in teaching and learning is high.